Electrochemical synthesis of nanostructured polyaniline: Heat treatment and synergistic effect of simultaneous dual doping. Issue 3 (27th November 2012) - Bhandari, Subhendu; Singha, Nikhil Kumar; Khastgir, Dipak
Abstract Different nanostructured polyaniline (PAni) has been synthesized via facile template‐free electrochemical synthesis approach in aqueous medium. Instead of conventionally used aniline, aniline sulphate was used in electrochemical polymerization. The synthesis process involves simultaneous doping with combination of inorganic and organic acid, i.e., sulfuric acid (H2SO4) and p‐toluenesulfonic acid (PTSA) at different ratios keeping total dopant concentration constant. Synergistic increase in conductivity is observed and the best conductivity is achieved at 3:1 ratio of [H2SO4]:[PTSA]. Different nanostructures of PAni are revealed through morphological analysis consisting of nanosphere, nanorod, and clustered particles among which finer nanorods show the best electrical conductivity. Upon controlled heat treatment followed by further cooling, resistivity increases, but after one day it decreases again and in the optimized dual doped PAni, it approaches approximately the same value of initial resistance. Lattice strain and benzenoid to quinonoid ratio increases with heat treatment. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013